Incidence and determinants of catastrophic health expenditures and impoverishment in Pakistan - Arif, Saima; Kishwar, Shabana; Shaikh, Salman Ahmed (Public health, 2021)
Objectives - Out-of-pocket (OOP) payment is a major health financing mechanisms across developing nations such as Pakistan. Private health expenditures are estimated to be 64.4%, of which 89% are OOP made by the households (National Health Accounts, 2015-16). These high health care expenditures cause households to face financial burden resulting in poverty. This study aims to estimate the incidence and determinants of catastrophic health expenditures and impoverishment for Pakistan. - Study design - Household-based cross-section study. - Methods - We used the data from the Household Integrated Economic Survey (2015-16 and 2018-19), carried out by the Pakistan Bureau of Statistics. The well known methodology developed by Wagstaff and Doorslaer was used in this study for estimating the incidence and impoverishment effect of catastrophic health spending. - Results - It is found that at 10% threshold (out of total consumption expenditures), catastrophic health payments are incurred by 4.51% and 13.15% of households for 2015-16 and 2018-19, respectively. Moreover, following the 40% threshold (out of non-food expenditures), this incidence is 0.45% and 4.57%. Poverty headcount was 23.28% and 18.43% gross of health payments in both the considered years, respectively, whereas it turns out to be 24.68% and 22.02% net of healthcare payments for the respective years, representing an increase in poverty headcounts of 1.4% and 3.59%. - Conclusion - OOP health payments exert pressure on household's capacity to pay and push them into poverty. This article recommends that the burden of OOP expenditures borne by households should be reduced to prevent them from falling into poverty by initiating some strategies (health financing policy reforms in terms of financial protection) with political support.